Long Non-coding RNA MRUL Contributes to Osteosarcoma Progression Through the miR-125a-5p/FUT4 Axis - Tian, Cong; Sun, Xingxing; Han, Kun; Zhu, Hongling; Min, Daliu; Lin, Shuchen (Frontiers in Genetics, 2020)
Osteosarcoma (OS) originates in the skeletal system and has a rising global incidence. Long Noncoding RNAs (lncRNAs) are key regulators of human cancers development and progression. However, their roles in the development of OS are not well understood. This research aimed to investigate the effect of a long noncoding RNA (lncRNA), MRUL, on OS and revealed its potential molecular mechanisms. The bioinformatics analysis demonstrated that lncRNA MRUL was involved in regulating nucleic acid-templated transcription, cellular macromolecule biosynthetic process, immune response, and inflammatory response. In this work, the expression of lncRNA MRUL was detected by quantitative real-time polymerase chain reaction (qRT-RCR) in both cancer tissues and cell lines. We found that lncRNA MRUL was up-regulated in cancer tissues and cell lines. Functional experiments showed that knockdown of lncRNA MRUL inhibited OS cell proliferation, and metastasis. At the same time, we found that lncRNA MRUL interacted with miR-125a-5p to suppress FUT4 expression. Moreover, inhibition of miR-125a-5p abrogated the biological roles of lncRNA MRUL knockdown on OS cell proliferation, migration, and invasion. In conclusion, these results demonstrated that OS-upregulated lncRNA MRUL promoted cell proliferation, and metastasis via negatively regulating miR-125a-5p, and imply that lncRNA MRUL may be a potential biomarker for OS.